Android Application-Based Management Model for Prevention and Handling of Violence in Schools - Supadi; Evitha Soraya; Winda Dwi Listyasari (Indonesian Values and Character Education Journal, 2025)
Acts of violence in the school environment are complex problems that can hinder the psychological and academic development of students. Although various policies have been issued, many educational units still lack a structured and responsive system for preventing and handling violence. This research aims to develop an Android-based application as a medium for assessing, educating, reporting, and managing violence in schools. This type of research is a form of research and development (R&D) that is carried out through the stages of preliminary study, planning, initial product development, limited field trials, product revision, and dissemination. The subjects in this study include IT experts, educators, and high school students. Data were collected through literature studies, interviews, and questionnaires, and then analyzed both quantitatively and qualitatively. The results showed that student involvement in positive activities was correlated with prosocial behaviour and improved academic achievement. In addition, educational units that implement more violence prevention strategies tend to have lower rates of violence. This study concludes that the development of an early detection instrument for potential violence and the design of an Android-based application have been successfully carried out. The implications of this study suggest that the use of digital applications can be a valuable solution in creating a safe, friendly, and inclusive learning environment.